Pharmacy deserts and COVID-19 risk at the census tract level in the State of Washington. (December 2022) - Wittenauer, Rachel; Shah, Parth D.; Bacci, Jennifer L.; Stergachis, Andy
Highlights: Pharmacy desert communities have worse access to key services like vaccination. In Washington State, over 450, 000 adults (8% of adults) live in pharmacy deserts. Those living in pharmacy deserts were also associated with higher risk for COVID-19. Several policy solutions are needed to address the access gap for pharmacy services. Abstract: Community pharmacies are a crucial component of healthcare infrastructure, including for COVID-19 pandemic prevention services like testing and vaccination. Communities that are "pharmacy deserts, " experience healthcare inequities. However, little research has characterized where these communities are, making it difficult for local leaders to prioritize resources for them. This study identifies pharmacy deserts at the census tract level in Washington state for the first time and explores their association with COVID-19 risk. Out of 1, 441 tracts, 127 were pharmacy deserts, comprising approximately 454, 000 adults, or 8% of the state's adult population. Among those tracts identified as pharmacy deserts, 67% were considered high risk for COVID-19. Solutions are needed to expand equitable access to pharmacy services in these communities. The methods and data presented herein provide healthcare leaders with information to address this pharmacy access gap in Washington and could be similarly applied to other settings. Three categories of policy changes could address health inequities found in our study: 1) improve financial incentives for pharmacists to practice in underserved areas, 2) prevent pharmacy closures, and 3) deploy innovative care delivery methods such as telehealth services.